Effect of Chronic Obstructive Pulmonary Disease on Interleukin-8 Level in Sputum and Peripheral Blood Neutrophils: A Case Control Study - Prashant Mani Tripathi; Surya Kant; Ravi Shanker Yadav; R.A.S. Kushwaha; Ved Prakash; Abbas Ali Mahdi; Abhishek Dubey (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is characterized by partially reversible airflow obstruction and chronic inflammation in the pulmonary as well as in systemic compartment. Interleukin 8 (IL-8) is one of the most potent inflammatory mediators and it is involved in the migration and activation of neutrophils. Previous studies demonstrated the increased levels of IL-8 in plasma and sputum of COPD, but peripheral blood neutrophils mediated IL-8 level including their relationship to smoking pack years and spirometric parameters is still unknown. Aim: To assess the levels of IL-8 in sputum and peripheral blood neutrophils of COPD patients and to compare them with healthy controls. Materials and Methods: This case control study was done from March 2014 to November 2016 in the department of respiratory medicine KGMU. A total of 81 COPD patients and 81 healthy controls were recruited in this study. Peripheral blood neutrophils were isolated from COPD patients and healthy controls and stimulated with Lipopolysaccharide (LPS). The neutrophils cell culture supernatant was assessed for IL-8 level using ELISA techniques, whilst IL-8 mRNA expression was measured using real-time polymerase chain reaction. Induced sputum was obtained from all participants and processed. The sputum supernatant was also assayed for IL-8 level. Results: COPD patients had significantly higher protein level of IL-8 in peripheral blood neutrophils (p=0.018) and sputum supernatant (p=0.011) compared to healthy controls. Gene expression of IL-8 was also significantly higher in peripheral blood neutrophils of COPD patients (p=0.001). In the patients with COPD, the smoke pack year was significantly correlated with the level of IL-8 in peripheral blood neutrophils (r=0.42; p=0.009) and sputum (r=0.48; p=0.002). The smoke pack years was found negatively correlated with FEV1 % predicted (r=- 0.37; p=0.044) and FEV1 /FVC (r=-0.47; p=0.007) in the COPD patients. Conclusion: The increased level of IL-8 in peripheral blood neutrophils and sputum support the hypothesis that COPD is a multicomponent disease. IL-8 level may be helpful in predicting development of COPD in smokers.